Mixed hummingbird: Long-proboscid-fly pollination in 'ornithophilous' Embothrium coccineum (Proteaceae) along a rainfall gradient in Patagonia, Argentina - Devoto, Mariano (2006)
The pollination ecology of eight populations of the tree Embothrium coccineum was studied along a steep rainfall gradient in NW Patagonia, Argentina. The showy red flowers suggest an ornithophilous pollination syndrome and they have been reported to attract hummingbirds in Argentina and hummingbirds and passerines in Chile. At each population, flower visitors were recorded and floral rewards were analysed. We found a highly significant increase in nectar concentration towards the drier end of the gradient, but this change was not related to the turnover of species in the flower-visitor assemblage of E. coccineum. In addition to the hummingbird Sephanoides sephaniodes (Green-Backed Firecrown, Trochilidae) which is widespread throughout the temperate forest at this latitude, other species seem to be locally important as pollinators of E. coccineum in some sites in Argentina (e.g. two long-tongued tanglewing flies (Nemestrinidae) of the genus Trichophthalma). The long-dated occurrence of tanglewing flies in South America, relative to the more modern hummingbirds, suggests that ornithophily may be a derived character in E. coccineum, the ancestral condition being pollination by Nemestrinidae.